Effects of adaptation to handling on the circadian rhythmicity of blood solutes in Mongolian gerbils. Issue 2 (14th May 2019) - Liu, Xingchen; Zheng, Xiang; Liu, Yihan; Du, Xiaoyan; Chen, Zhenwen
Abstract: The Mongolian gerbil has been widely used in many research fields and has been reported to be a diurnal laboratory animal. The circadian rhythmicity of these gerbils was investigated in the present study by measuring two hormones that show daily oscillations, cortisol and ACTH, in serum using ELISA kits. The levels of the two hormones were highest at 8:00am and their rhythmic changes were similar to those in humans. In addition, the influence of stress of handling and blood collection on the physiological parameters of the gerbils was examined. After adaptation to handling for 1 week, some serum parameters in the animals changed. Handling and blood collection did not impact significantly on the following parameters: creatine kinase (CK), lactate dehydrogenase (LD), alanine aminotransferase (ALT), aspartate transaminase (AST), blood urea nitrogen (BUN), and albumin (ALB). However, blood glucose (GLU), total protein (TP) and globulin (GLB) significantly increased while creatinine (CRE) and albumin/globulin (A/G) significantly decreased after adaptation. This work further confirms that the Mongolian gerbil is a diurnal animal and also indicates that a suitable adaptation procedure is necessary for getting reliable results when performing experiments using these animals.